2019
DOI: 10.1115/1.4042887
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation in Transient Flows Through a Micro-Nozzle

Abstract: High cavitating or supercavitating flows in fuel injector systems are crucial since they improve the mixing and the fuel atomization into combustion chambers, decreasing both fuel consumption and pollutant emissions. However, there is a lack of information regarding the required time to obtain high cavitating flows at the nozzle outlet, from the start of the injection pulse. In this work, a new method to quantify the time to get supercavitating flows at the nozzle outlet is developed. In particular, the delay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
1
0
2
Order By: Relevance
“…En el contexto del presente artículo se emplean tópicos fundamentales de la Mecánica Analítica, los cuáles actúan a modo de soporte para realizar el desarrollo del trabajo y explorar el alcance de la investigación. En este sentido, conceptos tales como coordenadas generalizadas, desplazamientos virtuales, principio de los trabajos virtuales y fuerzas generalizadas son fundamentales para la formulación de las ecuaciones de Lagrange en su forma más extendida [3]. Esta última afirmación refiere a la consideración de la parte no conservativa de las fuerzas no conservativas que intervienen en el dispositivo robótico.…”
Section: Marco Teóricounclassified
See 1 more Smart Citation
“…En el contexto del presente artículo se emplean tópicos fundamentales de la Mecánica Analítica, los cuáles actúan a modo de soporte para realizar el desarrollo del trabajo y explorar el alcance de la investigación. En este sentido, conceptos tales como coordenadas generalizadas, desplazamientos virtuales, principio de los trabajos virtuales y fuerzas generalizadas son fundamentales para la formulación de las ecuaciones de Lagrange en su forma más extendida [3]. Esta última afirmación refiere a la consideración de la parte no conservativa de las fuerzas no conservativas que intervienen en el dispositivo robótico.…”
Section: Marco Teóricounclassified
“…Si estas ecuaciones no dependen del tiempo, los desplazamientos reales coinciden con los virtuales [7]. Considerando un sistema de N partículas, el vector posición asociado a la partícula iésima se puede expresar en función del vector de coordenadas generalizadas q y del tiempo t de la forma: ri = ri (q, t) i = 1, 2,…, N. Suponiendo que la partícula experimenta un desplazamiento virtual δri, este se relaciona con los desplazamientos virtuales de cada coordenada generalizada δqk mediante la ecuación (3). Al considerar un sistema holónomo, si este posee n grados de libertad, esta cantidad coincide con la cantidad de coordenadas generalizadas.…”
Section: Desplazamiento Virtual Y Fuerza Generalizadaunclassified
“…The occurrence of cavitation within nozzles has a crucial impact on the flow field for various hydraulic systems such as dump throttles of liquid propellant rocket engines, orifices of hydraulic jacks, and injector nozzles of diesel engines [1][2][3]. Especially for the latter, many researchers have shown that cavitation within the nozzles significantly enhances the atomization of high-speed liquid jets [4], reduces jet breakup length [5,6], and increases jet spray angle [7,8]. Meanwhile, the damage risks of cavitation such as erosion and vibration will always be there during bubble collapse.…”
Section: Introductionmentioning
confidence: 99%